PELATIHAN TENTANG PENERAPAN TERAPI KOMPLEMENTER PIJAT BAYI DAN PERBAIKAN POLA MAKAN SEBAGAI UPAYA PENCEGAHAN STUNTING PADA ANAK BALITA DI WILAYAH KERJA PUSKESMAS TANAH KALI KEDINDING KOTA SURABAYA - Syuhrotut Taufiqoh; Aryunani Aryunani; Fulatul Anifah (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Public education can be done to improve health status of the community. One of the health problems that occur in children is stunting. The purpose of this community service activity is to increase knowledge, attitudes, and community behavior in preventing stunting with complementary baby massage therapy as well as improving diet. The results of the educational activities showed that the activities carried out according to the planned time contract with the target of toddler cadres in the working area of ​​the Tanah Kali Kedinding Health Center, Surabaya City. The results of the evaluation showed that the participants were on average active and very enthusiastic in participating activities. Furthermore, the cadres of toddlers can teach mothers of toddlers about the education that has been obtained. The application of complementary baby massage therapy and improvement of diet, parenting, and sanitation is expected to be carried out by mothers of toddlers with the assistance of toddler cadres as an effort to prevent stunting in children under five